Lenin, Hegel and western marxism : a critical study. - Anderson, Kevin (Urbana Chicago : University of Illinois Press University of Illinois Press, 1995)
Bibliotheek François Vercammen
Engels
Monografie
Keywords: Lenin, Vladimir; Hegel; marxisme